Use of QuantiFERON-TB Gold to determine the aetiology of idiopathic erythema induratum: A case report. (October 2018) - Brandon, Alisa; Mufti, Asfandyar; Sibbald, R. Garry
Although rare, erythema induratum is the most common entity presenting as lobular panniculitis with vasculitis. It is usually caused by a hypersensitivity reaction to Mycobacterium tuberculosis, although other aetiologies have been reported. We present a case of a 73-year-old male with multiple recurring tender erythematous nodules on the backs of both calves and shins. Prior to arrival in our clinic, the patient underwent a 9-month course of isoniazid with no improvement and subsequently received a diagnosis of idiopathic erythema induratum. We performed an interferon-gamma release assay QuantiFERON-TB Gold which was positive for M. tuberculosis infection. The patient was successfully treated with ethambutol 1.6 g for 1 month; pyrazinamide 2 g for 2 months; and isoniazid 300 mg, vitamin B6 25 mg, and rifampin 600 mg for 6 months. This case highlights the utility of using interferon-gamma release assay QuantiFERON-TB Gold and a multidrug regiment over isoniazid in erythema induratum.